Association of genetic polymorphisms of dipeptidyl peptidase-4 with Type 2 Diabetes Mellitus in Malaysian subjects / Radwan Hamoud Ali Ahmed - Radwan Hamoud, Ali Ahmed (2017)
The DPP4 gene encoding for dipeptidyl peptidase-IV (DPP-IV); also known as CD26, degrades glucagon-like peptide (GLP)-1 and is widely known for its regulatory effects in glucose metabolism. Elevated levels of soluble circulating form (sCD26/DPP-IV) are associated with an increased risk of developing metabolic syndrome (MetS) and type 2 diabetes mellitus (T2DM). DPP4 gene polymorphisms are thought to be genetic determinants of increased sCD26/DPP-IV; this may be a risk factor for T2DM. The aim of this study was to investigate the fasting serum levels of sCD26/DPP-IV and active GLP-1 in Malaysian subjects with T2DM (with and without MetS), as well as the associations between sCD26/DPP-IV levels with MetS and anti-diabetic therapy. Furthermore, this study was carried out to evaluate the association of genetic polymorphisms of DPP4 in Malaysian subjects with T2DM and to evaluate whether they had an effect on serum levels of sCD26/DPP-IV. The sCD26/DPP-IV levels, active GLP 1 levels, body mass index (BMI), glucose, insulin, A1C, glucose homeostasis indices, and lipid profiles at fasting state were assessed in 314 T2DM subjects (227 with MetS and 76 without MetS), 71 non-diabetic subjects with MetS subjects and 164 normal subjects without diabetes or MetS. The results obtained were analyzed with ANOVA, univariate and linear regression models. 10 DPP4 SNPs were genotyped, and their association with T2DM were evaluated by logistic regression controlled for age, gender and BMI. Fasting serum levels of sCD26/DPP-IV were significantly higher in T2DM patients with MetS (p = 1.2×10-4), and without MetS (p = 0.015) than in normal subjects. However, active GLP 1 levels were significantly lower in T2DM patients with MetS (p = 0.020) and without MetS (p = 0.028) than in normal subjects. In T2DM subjects, sCD26/DPP-IV levels were associated with significantly higher A1C levels (p = 0.009), but were significantly lower in patients using monotherapy with metformin (P = 0.041). Furthermore, sCD26/DPP-IV levels were negatively correlated with active GLP-1 levels in T2DM patients with MetS iv (p < 0.001), and without MetS (p < 0.001). This study revealed that obese non-diabetic subjects had reduced serum GLP-1 levels and elevated sCD26/DPP-IV levels with positively associated with insulin resistance. In normal subjects, sCD26/DPP-IV levels were associated with increased BMI (p = 0.023), cholesterol (p = 0.001), and LDL cholesterol (LDL-c) levels (p = 0.001). Association analysis data of DPP4 polymorphisms with T2DM in Malaysian subjects, showed that rs12617656 was significantly associated with T2DM in the recessive genetic model (OR = 1.98, p = 0.006), dominant model (OR = 1.95, p = 0.008), and additive model (OR = 1.63, p= 0.001). This association was more pronounced among Malaysian Indians, recessive (OR = 3.21, p = 0.019), dominant OR = 3.72, p = 0.003) and additive model (OR = 2.29, p = 0.0009). The additive genetic model showed that DPP4 rs4664443 and rs7633162 polymorphisms were associated with T2DM (OR = 1.53, p = 0.039), and (OR = 1.42, p = 0.020), respectively. On the other hand, the rs4664443 G>A polymorphism was associated with increased sCD26/DPP-IV levels (p = 0.042) in T2DM subjects.